(untitled) (diségno, 2020)
"Among Chuang-Tzu’s many skills, he was an expert draftsman. The king asked him to draw a crab. Chuang-Tzu replied that he needed five years, a country house, and twelve servants. Five years later the drawing was still not begun. ‘I need another five years’, said Chuang-Tzu. The king granted them. At the end of these ten years, Chuang-Tzu took up his brush and, in an instant, with a single stroke, he drew a crab, the most perfect crab ever seen”. [Calvino 1988, p. 53] Initially, when we thought up the program of side events with the members of the organising committee at the 41st International Conference of the Performance Disciplines/Congress of the Italian Drawing Union, hosted in 2019 by the University of Perugia and dedicated to the two-way relationship established between ar t and drawing, we thought of organising a sculpture exhibition. And, in particular, we imagined exhibiting en plein air, in the University gardens, replicas of three famous contemporary sculptures made with a 3D printer and characterised by provocative chromatic finishes. Sculptures like Dibuixar l’Espai by Pepe Diaz Azorin, The Man Who Measures the Clouds by Jan Fabre and Study of Perspective by Ai Weiwei.